Boll weevil within season and off-season activity monitored using a pheromone-and-glue reusable tube trap (Scientia Agricola, 2018)
The boll weevil colonizes cotton fields as early as cotton squaring, causing significant losses due to feeding and protected development inside fruiting structures throughout crop phenology. Successful control depends on control of adults and their accurate detection when they colonize the crops. The commercial trap and boll weevil attract-and-control tubes (BWACT) are the only available tools to monitor and attract-and-kill boll weevil, despite limitation in efficacy, and insecticide in BWACT is not allowed in organic production. A grandlure-and-glue reusable and insecticide-free tube (GGT) made with polyvinyl chloride tube, smeared with entomological glue, and lured with pheromone was tested to detect boll weevil activity across various seasons. Boll weevil showed activity during growing season and off-season from 2009 to 2012 in the Semiarid and with higher numbers captured in GGT in comparisons to commercial traps. GGT was able to detect early weevils in the field right after planting. Further, the overall averages resulted in 34-, 16.8-, and 7.5-times more weevils captured in GGTs compared to the traps during stalk destruction in the Semiarid 2011 and Cerrado season 2012/13 and during the harvesting period in the Cerrado season 2011/12, respectively. Therefore, boll weevils were captured actively during season and off-season and early captures obtained in GGT compared to traps showed a better correlation between captures and square damage.